Exploring Repetition Phenomena and Solution Strategies in Task-Based Teaching Method Research in School Physical Education - Yuxi Liu; Gang Song (Ilmu Inovasi Nusantara, 2025)
Task-based teaching is an innovative instructional model widely applied in high school physical education (PE) classrooms. It requires teachers to respect students' dominant role in teaching, organize diverse practical activities based on students' actual conditions and course content, ensure teaching quality and efficiency, and promote improving students' comprehensive physical literacy. This paper elaborates on the characteristics and roles of task-based teaching in high school PE courses and proposes specific application strategies. These include improving pre-class preparation, clarifying teaching objectives, creating teaching scenarios, optimizing classroom atmosphere, assigning problem-based learning tasks, guiding students' independent inquiry, respecting students' differences, setting hierarchical learning tasks, optimizing language expression methods, enhancing classroom teaching efficiency, and focusing on the expansion of learning tasks to improve students' comprehensive abilities. These strategies aim to enhance the effectiveness of high school PE course teaching. However, in academic research, especially in the niche market of school physical education, repetitive research on task-based teaching methods is common. This phenomenon wastes valuable research resources and affects the depth and breadth of academic innovation and knowledge accumulation. This paper aims to identify repetitive research in the study of task-based teaching methods in school physical education through a literature review, analyze their causes, and propose effective avoidance strategies